The Importance of Pragmatics in Teaching a Foreign Language - Habibullayevna, Ibodullayeva Umida (PT. Antis International Publisher, 2024)
This article examines the importance of pragmatics in language teaching, because the pragmatic aspect of learning is related to the formation of certain skills and competencies in students, the commonality of which allows for successful linguistic communication in the language being studied. In this case, the requirements for a specific type of speech activity and the level of mastery are different: it includes processes from teaching oral speech within a certain topic to comprehensive mastery of a foreign language.